Effect of Different Renovation Methods on the Productivity of Mid-Forest Meadows as Foraging Areas for Free-Living Red Deer Population - Jędrzej Daszkiewicz; Piotr Goliński (Agronomy)
Mid-forest meadows are integral to maintaining biodiversity and ecological services in forested landscapes but face degradation due to various reasons. This study evaluated the effectiveness of renovation methods on sward yield and herbage quality in two mid-forest meadows in northwestern Poland (54°10′ N, 16°78′ E), aiming to maintain their function as the foraging areas for the free-living red deer population. The results indicated that overdrilling was insufficient to significantly enhance sward quality or productivity (with no significant differences in DM yield between treatment and control), largely due to competition with existing vegetation and suboptimal habitat conditions. The full tillage method, in combination with sowing dedicated seed mixtures, substantially improved the sward yielding and forage quality, especially in terms of DM yield (av. 7% on object W; 18% on object TD). The efficacy of renovation methods varied between experimental sites, suggesting that the renovation strategy of mid-forest meadows should be tailored according to the habitat conditions.